Wing Interference Patterns in patterned wings of Culicoides Latreille, 1809 (Diptera: Ceratopogonidae)—exploring potential identification tool - Pielowska-Ceranowska, Agata; Szwedo, Jacek (Zootaxa, 2020)
Biting midges, nematoceran flies family Ceratopogonidae, is represented by more than 6200 valid species. This group is still poorly known and not easy in identification. Structural coloration of insect wings (WIP, or Wing Interference Pattern) is an example of an optical phenomenon called iridescence, which is based on the formation of pigment-free, rainbow colours caused by the interference of white light reflected from transparent or semi-transparent structures. Preliminary results indicate that the structural colouring of the wings of these insects may be helpful in the delimitation of closely related and cryptic species.